The protection of the marine environment and the prevention of oil pollution from ships under MARPOL 73/78 : a study with special reference to the Algerian practice - Bahaeddine, Bitam (2013)
The Convention on the Prevention of Oil Pollution from Ships, known on MARPOL 73/78, is the most important Convention for the protection of the marine environment from the risk of contamination caused by the illegal discharge of oil pollution from ships at sea. The Convention contains six Annexes. Annex I and Annex II are mandatory for any country that wants to join the Convention. However, the other four Annexes are optional. Annex I and Annex II of MARPOL 73/78 entered into force in 2 October 1983 and 6 April 1987 respectively. There are 156 states party to the Convention. MARPOL 73/78 imposes on the flag State to maintain the marine environment and to implement all the technical and legal obligations in order to avoid illegal discharge as well as accidents. For its part, the International Maritime Organization strives to protect the different maritime areas and the special marine areas that need specific and strict protection. It also seeks to prevent illegal discharge of oil in these areas, including the Mediterranean Sea. Algeria, which is located in the Mediterranean Sea, is a member of MARPOL 73/78. It shall take all the conditions that have been imposed by the Convention to protect the marine environment from illegal discharge whether in its territorial sea or the other maritime zones considered as special areas in Annex I and Annex V of the Convention. With the development of increased maritime trade, several of the risks have increased for the marine environment and its safety. Therefore, all member states of MARPOL 73/78 have to manage and implement the Convention effectively and diligently in order for MARPOL 73/78 to achieve its goals to protect the marine environment from the threat of illegal discharge of oil pollution from ships at sea on one hand, and to support maritime commerce on the other.